Program Planning In Course And Training Institutions Purwacaraka Music Studio Padang - Annisa Meidina Martha; Alim Harun Pamungkas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research was motivated by a course and training institution (LKP) Purwacaraka Music Studio Padang which has fairly stable course participants and good course participants' achievements in the midst of the covid-19 pandemic. This type of research is a case study with a qualitative approach. the main instrument of this research is the researcher himself. sources of data in this study were branch managers, LKP admins, tutors, course participants, and parents of course participants. Data collection techniques in this study were interviews, observation, and documentation. The validity of the data obtained from this research is by triangulation of data sources. The results showed that: LKP Purwacaraka Music Studio Padang did all the preparations for learning based on the direction of the central Purwacaraka Music Studio. The curriculum provided is based on the national standard of Indonesian music courses so that the preparation that must be done by course participants, the ability of tutors, the material taught, the media used, the methods used, the learning environment prepared for the convenience of visitors, and preparation for evaluation of the learning of course participants with national standards throughout the region Indonesia. This makes LKP Purwacaraka Music Studio course participants even in small areas able to compete at national and international levels.